2000
DOI: 10.1175/1520-0493(2000)128<2190:nsoasi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of Air–Sea Interaction under High Wind Conditions Using a Coupled Model: A Study of Hurricane Development

Abstract: In this study, a coupled atmosphere-ocean wave modeling system is used to simulate air-sea interaction under high wind conditions. This coupled modeling system is made of three well-tested model components: The Pennsylvania State University-National Center for Atmospheric Research regional atmospheric Mesoscale Model, the University of Colorado version of the Princeton Ocean Model, and the ocean surface gravity wave model developed by the Wave Model Development and Implementation Group. The ocean model is init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
131
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(140 citation statements)
references
References 47 publications
6
131
0
3
Order By: Relevance
“…With the extreme high winds, intense rainfall, large ocean waves, and copious sea spray the surface flux parameterization should be updated. This is illustrated by numerical simulation of air-sea interaction under high wind conditions using a coupled atmosphere-ocean-wave modeling system (Bao et al 2000). Improvement of WWATCH for high wind conditions needs finer resolution and more realistic parameterization for surface momentum flux.…”
Section: ) Summer Monsoon Season (Cycle 288)mentioning
confidence: 99%
“…With the extreme high winds, intense rainfall, large ocean waves, and copious sea spray the surface flux parameterization should be updated. This is illustrated by numerical simulation of air-sea interaction under high wind conditions using a coupled atmosphere-ocean-wave modeling system (Bao et al 2000). Improvement of WWATCH for high wind conditions needs finer resolution and more realistic parameterization for surface momentum flux.…”
Section: ) Summer Monsoon Season (Cycle 288)mentioning
confidence: 99%
“…Fairall et al (1994) clai- med that, without taking account of evaporating spray droplets or some other source of latent heat, the boundary layer of modeled tropical cyclones would evolve in an unrealistic manner. Kepert et al (1999), Bao et al (2000) and Bao et al (2011) investigated the impact of spray on hurricanes using a coupled atmosphere-ocean-wave model and found that spray increases the air-sea fluxes and hurricane intensity substantially. Sea spray and spume can enhance the air-sea enthalpy exchange (Andreas and Emanuel, 2001) and make the interaction between the sea and air in the surface boundary layer more complex (Doyle, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of various hurricane and air-sea interaction models are available in the literature, some including a very detailed and specific description of the influencing factors and realistic regional geographic features, e.g., a large hybrid model of hurricane Opal in the Gulf of Mexico suggested by Bao et al (2000). Yet, the conclusion made by the authors there was that a realistic hurricane evolution could be simulated without a 'physically faithful description of fluxes at the air-sea interface, so long as the amount of momentum and enthalpy fluxes from the model's lower boundary … is sufficient to sustain hurricane evolution'.…”
Section: Introductionmentioning
confidence: 99%